Challenges in implementation of MyGAP among paddy farmers - Nurul Izzati Mohd Ali; Nur Illyani Ibrahim; Kadaruddin Aiyub; Saraswathy Kasavan; Lam, Kuok Choy; Rusinah Siron (Penerbit Universiti Kebangsaan Malaysia, 2021)
Good agricultural practice (MyGAP) has been introduced as a guide in implementing sustainable agriculture, which concerns the economy, environment, and society in producing high-quality food that is safe to be consumed. The number of paddy farming areas that have been certified with MyGAP is still low. Hence, this study aimed to investigate the challenges of implementing MyGAP among the paddy farmers and proposing relevant actions, using the Sekinchan paddy field as a case study. Qualitative techniques were conducted by observations in the fieldwork and the interviews with eight paddy farmers and two officers from the technical department. By using qualitative content analysis, six challenges associated with the implementation of MyGAP were identified such as (1) complexity of MyGAP certification system, (2) inadequate knowledge, (3) lack of pro-environment behaviour among paddy farmer, (4) ineffective communication, (5) lack of technology and (6) lack of monitoring and enforcement. This paper's suggested relevant recommendation to provide a platform for developing and improving policy and guidelines in MyGAP. From the findings, some recommendations are put forward in the pursuit of MyGAP in Sekinchan. The findings contributed to a better understanding of where attention should be directed, and which recommendations would better impact the implementation of MyGAP among the paddy farmers.